Vaccination in the post-COVID era: lessons to be learned in Latin America - Del Carpio-Orantes, Luis; Zambrano-Sánchez, Gabriela (Frontiers in Immunology, 2025)
In this document we discuss the reality of COVID vaccination in Latin America, which has been uneven across the continent; however, some experiences with COVID vaccination have demonstrated a protective effect against the development of chronic manifestations of COVID, in the so-called post-COVID syndrome.